Cinnamon Extract Inhibit Lipids and Inflammation by Modulation of Transcription Factors: in vivo Model - Tuzcu, Zeynep; Orhan, Cemal; Şahin, Nurhan; Şahin, Kazım; Juturu, Vijaya (Lippincott Williams & Wilkins, 2017)
[Abstract Not Available]
American-Heart-Association's Arteriosclerosis, Thrombosis and Vascular Biology/Peripheral Vascular Disease Scientific Sessions -- MAY 04-06, 2017 -- Minneapolis, MN
Keywords: Inflammation and inflammatory markers; Lipids; Nutrition